The Issues About Digital Informed Consent in Clinical Research - Freade Akbar; Ray Wagiu Basrowi (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Introduction: Informed consent is a concrete form of moral and ethical values that urgently needs to be emphasized, especially in research that requires the role of humans as subjects and is commonly associated with experimental research. Informed consent itself consists of two forms of print and digital, along with the times many parties began to examine how the role of informed consent, the advantages and disadvantages between print and digital, the application of good digital informed consent, and how information about research should be conveyed to the research subject so that it is easy to understand and in accordance with moral and ethical standards. The purpose of this article is to address issues related to digital informed consent in clinical research.Methods: We conducted a search on the SpingerLink database in March 2022 to see various publications in the last 2 years related to electronic informed consent using keywords: digital, informed consent, research. Results: Total 4 articles as source of literature review. Recent research shows the tendency of research subjects to choose digital informed consent because content is easier to personalize, makes it easier to understand content that is only needed by the subject, and the ease of adding digital content in certain forms of media such as audio, and video into digital formats. From the researcher’s side will increase the active participation and number of study subjects, making it easier for long-term interaction, especially follow-up research. There are 4 types of informed consent based on utilization for research and 5 informed consent processes that must be carried out in clinical research, which is attempted using language that is easily understood by the research subject and dynamic for further research.Conclusions: Informed consent in any form constitutes the autonomy right of the subject. Digital formats provide better prospects in facilitating communication to research subjects. But this ease must be accompanied by the consistency of the application of the standard informed consent process, even in intervention studies with biological samples this is more stringent. Informed consent given to the subject must use language that is easy to understand, and transparent. The subject of the study is given the right at any time to exit the research. In the future, the issue of morals and ethics of research will grow, and more dynamic informed consent is needed, especially for interventional clinical research.